Raja Ali Haji and the Demythology of King's Power in Malay-Islam Political Thought and Its Articulations - Alimuddin Hassan Palawa; Muhammad Ansor; Imam Hanafi; Sofiandi Sofiandi (Prodi Tata Negara (Siyasah) IAIN Langsa, 2025)
Despite being one of the most significant political thinkers in the 19th-century Islamic Malay world, the scholarship discussing Raja Ali Haji's political ideas remains relatively limited. Existing works on Raja Ali Haji have primarily focused on his literary contributions, contextualizing them within studies of Malay manuscripts, socio-political history, sultanates, or his contributions to Malay literature in the archipelago. This article contributed to expanding the discourse on Raja Ali Haji by delving into his political thoughts concerning the relationship between rulers and the ruled through the concept of demythologizing royal authority in Malay Muslim political thought and practice. The author argued that while Raja Ali Haji's works do not directly deconstruct the Malay political culture regarding power transition systems, his political language demonstrated his creative endeavor to demythologize royal authority and power transition systems within the Malay political culture, which was rooted in lineage and the mystification of royal power. This article demonstrated that Raja Ali Haji not only encourages the demythologization of royal authority and lineage-based power transitions but also introduced rational political behavior as an articulation of modern Islamic Malay political thought.